The Effect of Flashcards on Students’ Descriptive Writing Skill at Grade VII of SMPN 1 Tanjungpinang: Pengaruh Penggunaan Flashcards terhadap Keterampilan Menulis Deskriptif Siswa Kelas VII SMPN 1 Tanjungpinang - Dinda Widianda; Elsa Ernawati Nainggolan; Rona Elfiza (Program Studi Pendidikan Bahasa dan Sastra Indonesia, FKIP, Universitas Halu Oleo Kampus Bumi Tridharma Andounohu Kendari, Provinsi Sulawesi Tenggara – Indonesia, 2026)
Descriptive writing is a core productive skill in junior high school English learning, yet students often find it difficult to generate ideas, select appropriate vocabulary, and organize descriptions coherently. This study aimed to determine the effect of flashcards on the descriptive writing skill of Grade VII students at SMPN 1 Tanjungpinang. The research employed a quantitative quasi-experimental design involving 72 students divided into an experimental class and a control class, each consisting of 36 students. Data were collected through pre-test and post-test writing tasks assessed using a rubric covering generic structure, content, organization, vocabulary, grammar, and mechanics. The data were analyzed using descriptive statistics, Shapiro-Wilk normality test, Levene's homogeneity test, and Mann-Whitney U test because the data were not normally distributed and not homogeneous. The results showed that the experimental class improved from a mean score of 55.25 in the pre-test to 94.75 in the post-test, while the control class increased from 41.89 to 48.81. The Mann-Whitney U test for the post-test produced p < .001, indicating a significant difference between the two groups. These findings suggest that flashcards helped students expand vocabulary, generate ideas, and organize descriptive texts more effectively. The study contributes to English language pedagogy by providing empirical support for visual media as a practical strategy for improving descriptive writing in EFL classrooms.